THE EFFECT OF ENVIRONMENTAL BUDGETS AND TRANSPORTATION ON CARBON DIOXIDE EMISSIONS IN INDONESIA FROM AN ISLAMIC ECONOMIC PERSPECTIVE, 2004-2023 - Apersyah, Denara; Fuadi, Fatih; Ermawati, Liya (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
Global warming, caused by the increase of greenhouse gases (GHGs) in the atmosphere, is one of the most pressing issues of the 21st century. Carbon dioxide (CO2) emissions, one of the main sources of greenhouse gases, are increasing annually. Transportation and environmental budgets are two of the many factors that influence the quantity of carbon dioxide emissions. This study aims to investigate the relationship between carbon dioxide emissions and transportation and environmental budgets. Multiple linear regression analysis is the quantitative tool used in this investigation. The population studied includes Indonesia and covers 20 years, from 2004 to 2023. The results of the analysis indicate that while motorized traffic in particular contributes significantly to the increase in carbon dioxide emissions in Indonesia, environmental budgets have no discernible impact on these emissions. This study is expected to be useful for various stakeholders, including the general public, scientists, and the government as policymakers.